Napper cycling typology: Identifying and understanding different bicycle trip purposes. (January 2023) - Napper, Robbie
Highlights: Cycling literature is explored for examples of trip purposes. Six trip purposes are identified: recreation, commute, tasks & errands, passenger, work, sport. A typology is drawn to relate the six trip purposes to one another. The typology provides a better understanding of bicycle trips. Abstract: What is a bicycle trip? Our own experiences, observation and reading tells a story – that there is no single or all encompassing "cycling" activity. Although trip purposes are used as examples to illustrate findings or explain ideas, they are often limited to a binary of "transport or recreation". This oversimplification makes it easy to dismiss and mischaracterise cycling, particularly in countries with low or emerging cycling volumes. This research addressed this gap in knowledge with the development of a typology of bicycle trips. Based on six types of trips, the typology represents how they relate to, and mix with, one another. The typology represents a departure from a tendency of classifying people, to classifying the things they may do. The six journey types are: recreation, commute, tasks and errands, passenger, work, and sport. The implications of trip purposes are discussed, with opportunities arising such as a better understanding of what might be needed to encourage a modal shift from recreational to commuter riding, or a better understanding of user needs in different trips. The practical implications of trip purposes, for example riding with shopping and making short multi-stop journeys carrying goods and children raise implications for the bicycle transport system. This typology provides an addition to the transport lexicon to recognise the many utility functions, and benefits of cycling.